MBKM DAN KREATIVITAS PENGAJAR DALAM PENGEMBANGAN MATERI AJAR DI PERGURUAN TINGGI ISLAM - hasanah, ida faridatul; Hasanah, Uswatun; Syarif Zain, Zaki Faddad (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The education transformation has been developed continuously through the advancement of technology which determines the industrial era of 5.0 occurred due to the impact of the 4.0 revolution. The government and universities have carried out various policies and studies to obtain relevant innovations in teaching, training, and education in universities in response to these challenges. One of the policies launched by the Indonesian Government was Merdeka Belajar Kampus Merdeka (MBKM). The aim of the research is to examine the essence of the MBKM concept and the urgency of teachers’ creativity in Islamic Higher Education. This research is library research using content analysis techniques to analyze research data. The results of the study show that the development of learning materials in Islamic Higher Education affects the quality of learning, as the creativity of teachers is essential in developing teaching materials. Furthermore, this capability must continue to be optimized to make the MBKM program successful in Islamic Higher Education. Therefore, teachers should be able to optimize and develop learning materials, online information and resources, digital-based networks and communications, and collaborate with many different skill elements, regardless of distance and time.